EDUCATION POLICY ANALYSIS: EFFECTIVENESS AND EFFICIENCY OF TNI EMPOWERMENT AS TEACHERS IN 3 T AREA ( FRONTIER, REMOTE,UNDERDEVELOPED) - Muhammad Khairul Rijal Rijal (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
The many problems of education in Indonesia, need fast and right efforts from the government, especially policyholders in the education sector. The dynamic world of education requires the presence of effective and efficient education policies. One of the problems of education in Indonesia is the implementation of education in “ 3 T “ Areas (Frontier, Remote, And Underdeveloped ), where there is a shortage of teachers. To solve that problem, the ministry of education and culture create “ Maju Bersama Mencerdaskan Indonesia Program “ (MBMI) where one of the program contents is empowerment the bachelor’s degree to teach in 3 T areas. Certainly, this is a short-term solution, because they become teachers only one year in that area. Not only that, but the government also empowers the army as the teacher in 3 T areas. Empowerment of the army as the teacher leaves a problem about the function of the army in army and police laws. Furthermore, the professionalism of the army as the teacher is doubtful. How much effectiveness and efficiency this policy will try to analyze with SWOT analysis.